The relationship of psychological characteristics of drivers and driving style - Astreika, Natallia S. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
Under the psychological characteristics of driving style should be considered factors such as neuroticism, psychoticism, aggressiveness, depression, conscientiousness, aesthetic sensibility, femininity, disinhibition, total activity, timidity (shyness), sociability, mental instability, asocial, introversion and senzitivnost. To conduct the study, the following methods: multidimensional driving style inventory (A. Taubman-Ben-Ari adaptation I. A. Furmanov and N. S. Astreyko), psychodiagnostic test (V. Melnikov, L. Yampolsky). The sample for this study consisted of respondents aged 18 to 76 years (mean age – 31.4 years) in the amount of 260 people. Regardless of the gender analysis has identifed a number of positive and negative correlations between psychological characteristics and driving style.